Pro dan Kontra terkait Pidana Penjara dan Pidana Non-Penjara - Lilis Lisnawati (Universitas Budi Luhur, 2017)
Imprisonment for misdemeanors has stirred debate in Indonesia. The imposition seemed to deny the existence of probation, fines, diversion, community service, and rehabilitation as legally recognized forms of criminal punishment. However, implementing alternative punishments that do not involve imprisonment is also criticized for having several loopholes. Through a literature review, this paper examines the pros and cons of implementing imprisonment and alternatives to imprisonment from the perspective of academics. Individual, social, and governmental aspects of the benefits and drawbacks are examined.